Types and Meanings of Compound Words Found in Medical Textbook Entitled Gray’s Basic Anatomy - Mita Yanti, Ni Kadek (Humanis; Vol 22 No 4 (2018)DO - 10.24843/JH.2018.v22.i04.p36, 2018)
The title of this study is “Types and Meanings of Compound Words Found in Medical Textbook Entitled Gray’s Basic Anatomy”. This study aims to identify the types and analyze the meanings of compound words found in a medical textbook entitled “Gray’s Basic Anatomy”. The data of this study were collected by using documentation method with note taking technique. This descriptive qualitative study used two theories to analyze the data. The types of compound words were identified by using the theory of compounding proposed by Plag (2003). Meanwhile, the types of meaning of the compound words were analyzed based on the theory of meaning proposed by Ulmmann (1972). After analyzing the data, three types of compound words were found in the medical textbook entitled “Gray’s Basic Anatomy”, they are nominal, adjectival, and neoclassical compounds. Nominal compounds found totaled 37 while adjectival compounds found totaled 42 and neoclassical compound found totaled 135 out of 214. However, verbal compounds were not found in this medical textbook. Based on the analysis of meaning, two types of meaning were found in this medical textbook, they are transparent and opaque meaning. The compounds which have transparent meaning totaled 197 while the compounds which have opaque meaning only totaled 17.